Labor Camp Surveys in GCC Countries: Group Quarter Subsampling - Kien T. Le (14151537) (2019)
The Gulf Cooperation Council is a regional cooperation of six Middle Eastern countries—Saudi Arabia, Kuwait, the United Arab Emirates, Qatar, Bahrain, and Oman. A common feature of these countries is the existence of many group quarters, usually called labor camps, a term used to refer to housing accommodations for unskilled migrants where nonrelated people live together. The camp size ranges from a few people to a few thousand people from many different countries who speak dozens of languages. Also, the camp size and the composition of residents inside the camps change relatively quickly as people move in and out of the camps as their labor contracts expire or project needs change. This article presents one way to subsample this dynamic population inside such labor camps. The technique was used in one survey conducted in Qatar, where more than half of the country’s population resides in labor camps. Other Information Published in: Field Methods License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/1525822x18815416